2018
DOI: 10.1016/j.stem.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Reprogramming of Alpha Cells into Beta Cells, Induced by Viral Gene Therapy, Reverses Autoimmune Diabetes

Abstract: Successful strategies for treating type 1 diabetes need to restore the function of pancreatic beta cells that are destroyed by the immune system and overcome further destruction of insulin-producing cells. Here, we infused adeno-associated virus carrying Pdx1 and MafA expression cassettes through the pancreatic duct to reprogram alpha cells into functional beta cells and normalized blood glucose in both beta cell-toxin-induced diabetic mice and in autoimmune non-obese diabetic (NOD) mice. The euglycemia in tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 68 publications
10
149
0
Order By: Relevance
“…Several studies have suggested that human α-cells in islets can be reprogrammed to become β-cells 42,120 . Changes in α-cell to β-cell ratios and the appearance of cells positive for both glucagon and insulin have provided some evidence for such conversions; however, in the absence of lineage tracing, direct evidence is still lacking.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that human α-cells in islets can be reprogrammed to become β-cells 42,120 . Changes in α-cell to β-cell ratios and the appearance of cells positive for both glucagon and insulin have provided some evidence for such conversions; however, in the absence of lineage tracing, direct evidence is still lacking.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Focused studies of these β-cells in human samples and deeper understanding of the heterogeneity of human β-cells may eventually yield molecular targets that allow the production of functional insulin-secreting cells that resist autoimmunity. β-Cells derived from reprogramming of α-cells have been shown to resist autoimmunity in mouse studies, providing another potential path to study and possibly produce autoimmune-resistant β-cells 120 . Finally, it may be possible to genetically modify β-cells so that they are able to avoid detection or elimination by the autoimmune cells.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…The vectors generated in our study could be used for gene therapy of diabetes by delivering transcription factors or small hairpin RNAs (shRNA) into pancreatic islet cells. The overexpression or inhibition of several transcription factors, such as Pdx1, Ngn3, MafA , Pax4, and Arx was found to effectively convert pancreatic islet progenitors and committed islet α-cells into β-cells (Chakravarthy et al, 2017;Collombat et al, 2009;Furuyama et al, 2019;Matsuoka et al, 2017;Wang et al, 2018;Xiao et al, 2018;Zhang et al, 2016). Moreover, expression of other factors, such as Igf1 and Follistatin has also shown promise in preserving β-cell mass or protecting newly transplanted donor islets from apoptosis (Mallol et al, 2017;Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Over a period of 30 weeks, this gene therapy strategy was successfull in counteracting progression to autoimmune diabetes. Another strategy for the treatment of diabetes is the conversion of glucagon producing α-cells or other endocrine or exocrine pancreatic cell types into β-cells by overexpression or repression of certain transcription factors, such as Pdx1, Ngn3, MafA , Pax4, and Arx (Chakravarthy et al, 2017;Collombat et al, 2009;Courtney et al, 2013;Furuyama et al, 2019;Lima et al, 2016;Matsuoka et al, 2017;Wang et al, 2018;Xiao et al, 2018;Zhang et al, 2016) (for a review see (Vieira et al, 2016)). For the studies that utilized rAAV for gene delivery into murine islet cells, AAV8 had been used as this serotype was shown to be efficient for transduction.…”
Section: Introductionmentioning
confidence: 99%
“…In such mouse models, many potential therapeutics demonstrate great effects in preventing the development of disease, ameliorating the disease symptoms, or even curing the fulminant autoimmunity 15 . However, when applying therapeutics in translational medicine, clinical trials often are disappointing, demonstrating low or short-lived efficacy 68 .…”
Section: Translational Treatments Of Autoimmunity Often Do Not Reflecmentioning
confidence: 99%